TEORI KOMUNIKASI HADITH - Syamsuri Syamsuri (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2013)
Hadith becomes the media of communication about the power of khalilah who affirmed his power by the Hadith of the Prophet. Muslim community exerted their loyalty to the authority of Islamic teachings. Then, khalilah continued the authority of da'wah to strengthen and perpetuate his power. The support of Muslim from Arab tribes and peninsula drives the expansion of da'wah to the world. The "journalists" of Hadith such as Bukhari, Muslim, Abu Dawud, Ibn Majah, al Turmudhi and others voluntarily travelled from one province to another province ruled by Islam to find the accuracy of data in hadith collection. Through reporting investigation, the chain of sanad in accepting the hadith from the Prophet to the transmitter (rawi) was formed. The books of hadith collection contained sociological reality of khilafah's civilization